Intramolecular and Intermolecular Interaction Switching in the Aggregates of Perylene Diimide Trimer: Effect of Hydrophobicity - Peiyuan Su; Guangliu Ran; Hang Wang; Jianing Yue; Qingyu Kong; Zhishan Bo; Wenkai Zhang (Molecules, 2023)
The research on perylene diimide (PDI) aggregates effectively promotes their applications in organic photovoltaic solar cells and fluorescent sensors. In this paper, a PDI fabricated with three peripheral PDI units (N, N’-bis(6-undecyl) perylene-3,4,9,10-bis(dicarboximide)) is investigated. The trimer shows different absorption and fluorescence properties due to hydrophobicity when dissolved in the mixed solvent of tetrahydrofuran (THF) and water. Through comprehensive analysis of the fluorescence lifetime and transient absorption spectroscopic results, we concluded that the trimer underwent different excited state kinetic pathways with different concentrations of water in THF. When dissolved in pure THF solvent, both the intramolecular charge-transfer and excimer states are formed. When the water concentration increases from 0 to 50% (v/v), the formation time of the excimer state and its structural relaxation time are prolonged, illustrating the arising of the intermolecular excimer state. It is interesting to determine that the probability of the intramolecular charge-transfer pathway will first decrease and then increase as the speed of intermolecular excimer formation slows down. The two inflection points appear when the water concentration is above 10% and 40%. The results not only highlight the importance of hydrophobicity on the aggregate properties of PDI multimers but also guide the further design of PDI-based organic photovoltaic solar cells.